Is the Red Dragon Green? An Examination of the Antecedents and Consequences of Environmental Proactivity in China - Walker, Kent (Journal of business ethics, 2014)
China is the world’s second largest economy and the largest emitter of carbon dioxide, yet we know little about environmental proactivity in the most populated country in the world. We address this gap through a survey of 161 Chinese companies with two respondents per firm (N = 322), where we seek to identify the antecedents and consequences of environmental proactivity. We identify two categorizations of environmental proactivity: Environmental operational improvements and environmental reporting. We find that ecological motivations and regulatory stakeholder pressure are positively related to both types of environmental proactivity, and external stakeholder pressure is negatively related to environmental reporting. Furthermore, we find that (1) if a firm is environmentally proactive (as it relates to either measure) and they are ecologically motivated, there is a positive and significant cost advantage, and (2) if a firm makes use of environmental operational improvement and they are competitively motivated, there is a positive and significant reputation advantage. Implications for researchers, managers, and policy-makers in China are discussed.